A talk with a French speaker / Seng Hui Zanne and Muhammad Usamah Mohd Ridzuan - Seng, Hui Zanne; Mohd Ridzuan, Muhammad Usamah (Academy of Language Studies, 2023)
The French Language Club of Universiti Teknologi MARA Cawangan Pulau Pinang held its first cultural and intercultural talk via Google Meet on the 12th of December 2022 from 6:00 p.m. to 7:00 p.m. The main purpose of the talk was to share, from a French speaker's perspective, experiences and insights, about "Francophony" cultures. A French native speaker, Mr. Julien Pierre Bigot was invited as a guest speaker to share his personal thoughts on French and "Francophony" cultures. Mr. Julien graduated from Université Paul Verlaine, France, and has been teaching French as foreign language (FLE) for more than 20 years in Malaysia. He has vast experience working with Malaysian schools and university students. The talk began with an opening speech by the moderator, Miss Aliah Maisarah. The speaker then commenced his session by introducing himself and his profession. Throughout the sharing session, Mr. Julien conveniently related his past experiences of intercultural issues and current practices by the French teachers' community. Emphasizing on the diversity of French language(s) and culture(s), that originated from different French-speaking countries, the speaker exemplified his remarks with real situations that occurred in the Malaysian French language education landscape. Finally, a quiz was held for the students and the top 3 winners received a Texas Chicken meal voucher each as the reward.